Evidence for the progressive nature of neoplastic transformation in vitro. - Barrett, J C (1978)
The temporal acquisition of in vitro phenotypes associated with neoplasia were examined after exposure of Syrian hamster embryo cells to a chemical carcinogen. Quantitative assays measuring morphological changes, enhanced fibrinolytic activity, and anchorage independent growth were used to detect the development of transformed cells within a population of normal hamster embryo cells. Morphological transformation and enhanced fibrinolytic activity were early changes observed after treatment with benzo[alpha]-pyrene, whereas the ability to grow in semisolid agar was delayed 32-75 population doublings after carcinogen exposure. This delay was not due to selection of a small number of cells that were present early after treatment but at a level below detection, because a large percentage of the cells isolated at early passage (10(3)-fold above the level of detection) developed the potential for anchorage independent growth at later passages. This development of the anchorage independent growth phenotype was induced by the carcinogen treatment, because spontaneous transformation was rare. These observation suggest that multiple cellular changes are required for the acquisition of the capacity for anchorage independent growth and that neoplastic transformation in vitro is a progressive process through qualitatively different stages. Thus, an analogy can be drawn to the progressive nature of in vivo carcinogenesis. These results strongly justify the study of oncogenesis in cell culture as a model for neoplastic transformation in vivo.